RANCANG BANGUN ALAT UKUR INTENSITAS CAHAYA UNTUK MENENTUKAN SUDUT PUTAR JENIS SUATU BAHAN BERBASIS MIKROKONTROLER AVR ATMEGA8535 - Ria Amitasari; K. Sofjan Firdausi (Youngster Physics Journal, 2012)
ABSTRACT The Research has been conducted to design and realize an instrument for measuring the intensity of light to determine the specific rotation of  material based to microcontroller AVR ATmega8535. The specific rotation to determine the type of optical properties of a material. Measuring instruments using LDR as light sensors acquired using a microcontroller. Light intensity are displayed using LCD. Light intensity was measured to obtain the polarization angle (θ) based on the law of Malus. The specific rotation (α) obtained from the change polarization angle due to the material passing through 1 cm at each change of concentration of sugar solutions. The source of light was halogen lamp 50 watt. Materials used for polarization calibration tool are solutions of sugar. The study producing an instrument measuring the intensity of light that can be used to determine the optical properties of materials based on the specific rotation using the law of Malus. Measuring instrument of light has been calibrated with standards Luxmeter Lutron LX 101 and gave linier with a correlation coefficient of 0.99. The instrument produced specific rotation of sugar (54.17 ± 2.16) o/dm(g/mL) and gave linier correlation coefficient of 0.99. Key words: optical properties, specific rotation, the law of Malus, light intensity, LDR,  microcontroller,LCD